Model Antrian Pada Layanan Teller Bank Nagari Cabang Pembantu Universitas Negeri Padang - Nadya Nadya; Dony Permana (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Queues are people or goods that are waiting in line to become served. This queue usually occurs because many customers want to be served while the number of services is very limited, so customers who come cannot be served immediately because the service is busy. Long queues or too long waiting times will certainly harm the Bank or customers. The purpose of this study is to obtain an appropriate queuing model based on the characteristics of customer arrivals and queuing system performance measures in the queuing model contained in the service system that is in the teller section of Bank Nagari Padang State University Branch. From the results of the study showed that the queue system of the general teller section of Bank Nagari Assistant of Padang State University Branch followed the model (M / M / 1) :( GD /∞ /∞), the level of service usefulness (ρ) was 0.9797, the opportunity for servants not serving 0 , 0203, the average number of customers in the queue (Lq) is 47 customers, the average time the number of customers in the queuing system (LS) is 48 customers, the average time customers can spend waiting in a queue (Wq) is 140 minutes, and the average time a customer can spend waiting in the system (Ws) is 143 minutes. Keywords: Queueing, QueueingModel, Bank Services